Chicken Egg Price Prediction Using Extreme Gradient Boosting Method - Wahyudiputra, Helmy Fauzan; Witanti, Wina; Abdillah, Gunawan (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2024)
Prediction is a way to find out future data by looking at previous data patterns. Chicken eggs are one of the ingredients people need to fulfill their daily needs. There are many types of chicken eggs ranging from omega 3 eggs, purebred chicken eggs, free-range chicken eggs, and domestic chicken eggs. In this research, we will make a prediction on the price of purebred chicken eggs, especially in the local market, which sometimes experiences price increases and there can also be sudden price drops. With the XGBoost or Extreme Gradient Boosting method, research on predictions can be carried out because this method can identify trends or patterns in time series, where this method can interpret data that changes over time. This research aims to create a prediction system for the price of purebred chicken eggs using the Extreme Gradient Boosting method to produce accurate predictions.